The public health system in France and the structural developments during the last ten years. (13th November 2019) - Arwidson, P
Abstract: In 2009, the hospitals, health and territories act has entrusted the responsibility for care and public health to the regional health agencies. This decentralisation aims to adapt strategies to local situations. These regional agencies have a very strong autonomy. In 2013, it was stated in the national health strategy that it was necessary to develop a scientifically based prevention. Two tracks are to be followed: either by importing and adapting validated or promising programs by identifying effective programs in the international literature; or from existing French initiatives (tobacco, alcohol, psychoactive substances, physical activity). The high prevalence of smoking motivated the establishment of a National tobacco reduction program in 2014, which was then relayed by a national tobacco control program. In 2016, the Health System Improvement Act created a major national public health agency combining surveillance, prevention, health promotion and emergency response. The motivation was to achieve greater synergy and collaboration between the different functions in public health. A report from the Inspectorate General of Social Affairs has recommended that this agency should establish a national portal with evidence-based prevention and health promotion programmes. Established in 2018, the Priority Prevention Plan is a major interdepartmental project to improve the health of the population, and is part of the National Health Strategy. This interdepartmental approach reflects the Government's desire that all ministries should be able to contribute to prevention and health promotion. The increased investment in prevention and health promotion is starting to bear fruit with 1.6 million fewer smokers between 2016 and 2018. Immunisation coverage has also been improved. NutriScore, a nutritional information on the front of food containers, very easy to understand, has been put in place with partnership with 100 companies.